A elaboração de uma proposta metodológica interdisciplinar para análise de um estudo de caso voltado ao desenvolvimento rural - Pinto, Leonardo de Barros [UNESP]; Bianchi, Vinícius Rafael [UNESP]; de Oliveira, Sandra Cristina [UNESP] (My University, 2017)
One of the great challenges of higher education is the construction of interdisciplinarity. The difference and the evolution of disciplinary, multidisciplinary and interdisciplinary visions contribute to the understanding of the interdisciplinary construction process. The disciplinary knowledge can leave gaps in the treatment of research data, due to the specificities which is limited. The multidisciplinarity has broader view, but keeps parallel to other areas of knowledge. With the interdisciplinarity there are greater possibilities to fill gaps left by watertight approaches. In this work, there is the effort to show how, by merging methodologies, many gaps or new possibilities of analysis can be completed.
The establishment of a proposal methodology interdisciplinary for analysis of a case study oriented development
Keywords: Interdisciplinarity; Qualitative Methodology; Quantitative Methodology; Scientific methodology